If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4z + 3 + -1z = -6z + 7 Reorder the terms: 3 + 4z + -1z = -6z + 7 Combine like terms: 4z + -1z = 3z 3 + 3z = -6z + 7 Reorder the terms: 3 + 3z = 7 + -6z Solving 3 + 3z = 7 + -6z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '6z' to each side of the equation. 3 + 3z + 6z = 7 + -6z + 6z Combine like terms: 3z + 6z = 9z 3 + 9z = 7 + -6z + 6z Combine like terms: -6z + 6z = 0 3 + 9z = 7 + 0 3 + 9z = 7 Add '-3' to each side of the equation. 3 + -3 + 9z = 7 + -3 Combine like terms: 3 + -3 = 0 0 + 9z = 7 + -3 9z = 7 + -3 Combine like terms: 7 + -3 = 4 9z = 4 Divide each side by '9'. z = 0.4444444444 Simplifying z = 0.4444444444
| 15x-93=8x-23 | | 4(.5)+4y=25 | | 15(x+13)=-8(x-10) | | 5n^2+38n-16=0 | | x+2(4x)=5 | | 12=12r+24 | | (1/20)x=(1/5)x | | 8=2y-18 | | 5x+22=47 | | 18x^2-72xy+72y^2=0 | | -3n+7=-7-n | | 75=25+5d | | √(45/7y). | | 5(2x-8)+15=15 | | 5(2x-8)+15=10 | | 3x-3=6x+-12 | | x(x-1)=13 | | 8r-10=4r+10+8r | | 12x=4(3x-2) | | V(9v+1)=8 | | -6+19(x+16)=13 | | (2x)-(4/x)=6 | | -5-2s=3s | | 26-8t=30 | | 77-2x=117-7x | | 7x-4(4x+3)=42 | | -8u-6=10-10u | | r(11r+1)=10 | | X/2-3=x-4 | | 18-3r=-6 | | [X/4-3]=4 | | 10k-6=2+9k |